2004
DOI: 10.1086/380642
|View full text |Cite
|
Sign up to set email alerts
|

Association of Clinical Signs and Symptoms with Bacterial Findings in Acute Otitis Media

Abstract: In acute otitis media (AOM), a means of prediction of the bacterial pathogen based on symptoms and signs would be valuable in selecting appropriate antimicrobial treatment. Children in the control arm (n=831) in the Finnish Otitis Media Vaccine Trial were prospectively observed in a study clinic setting from the age of 2 to 24 months. In patients with AOM, myringotomy with aspiration was performed, and middle ear fluid samples were cultured for bacterial pathogens. Symptoms and signs of respiratory infections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
2
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(93 citation statements)
references
References 22 publications
5
80
2
4
Order By: Relevance
“…However, a number of other trials have explored the effect of induced ear discharge (myringotomy) -they showed worse 24-hour outcome but no difference in 7-day resolution or longer-term outcomes. [18][19][20] The present finding that about 60% of cases have an identifiable bacterial cause is entirely consistent with previously published data, 19 as is the range of bacteria identified, [19][20][21][22] although it was not possible to find any other UK data subsequent to the most recent changes in vaccine policy. No studies suggest that bacterial and viral infection can be distinguished on the basis of clinical presentation without microbiology.…”
Section: Comparison With Existing Literaturesupporting
confidence: 92%
See 1 more Smart Citation
“…However, a number of other trials have explored the effect of induced ear discharge (myringotomy) -they showed worse 24-hour outcome but no difference in 7-day resolution or longer-term outcomes. [18][19][20] The present finding that about 60% of cases have an identifiable bacterial cause is entirely consistent with previously published data, 19 as is the range of bacteria identified, [19][20][21][22] although it was not possible to find any other UK data subsequent to the most recent changes in vaccine policy. No studies suggest that bacterial and viral infection can be distinguished on the basis of clinical presentation without microbiology.…”
Section: Comparison With Existing Literaturesupporting
confidence: 92%
“…No studies suggest that bacterial and viral infection can be distinguished on the basis of clinical presentation without microbiology. 21,22 Although one paper suggests that bacterial findings are poorly correlated L Smith, P Ewings, C Smith, et al…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…[134][135][136] As for clinical findings in cases with S pneumoniae and nontypeable H influenzae, some studies suggest that signs and symptoms of AOM caused by S pneumoniae may be more severe (fever, severe earache, bulging TM) than those caused by other pathogens. 44,121,137 These findings were refuted by results of the studies that found AOM caused by nontypeable H influenzae to be associated with bilateral AOM and more severe inflammation of the TM. 96 High-dose amoxicillin will yield middle ear fluid levels that exceed the minimum inhibitory concentration (MIC) of all S pneumoniae serotypes that are intermediately resistant to penicillin (penicillin MICs, 0.12-1.0 μg/mL), and many but not all highly resistant serotypes (penicillin MICs, ≥2 μg/mL) for a longer period of the dosing interval and has been shown to improve bacteriologic and clinical efficacy e982 FROM THE AMERICAN ACADEMY OF PEDIATRICS compared with the regular dose.…”
Section: Microbiologymentioning
confidence: 99%
“…En este caso, existe demostración clara que la otorrea es más frecuente en las otitis de origen bacteriano, así como también es más frecuente el aislamiento de bacterias en las muestras timpánicas de menores de 2 años, y en pacientes con compromiso bilateral 10 .…”
Section: Comentarios Acerca De Los Resultadosunclassified